Edukasi Hipertensi dalam Upaya Pencegahan Dini Penyakit Tidak Menular di Kabupaten Karanganyar - Muslimin, Ahmad; Khotimah, Husnul; Aprilia, Sinta (IMPACT: Journal of Community Service, 2025)
Hypertension is a condition in which a person experiences an increase in systolic and diastolic blood pressure. Hypertension occurs from young to old age. Hypertension is the leading cause of death in the world. The results of the RISKESDAS survey show that the prevalence of hypertension reaches 34.1% with a target of 30.8%. These results are spread across various regions including Karanganyar Regency. Karanganyar Regency is one of the regencies with a high prevalence of hypertension. The results of 2018 data show that the number of hypertension in Karanganyar Regency aged 18 years and over reached 30,160 spread across 21 health centers in Karanganyar Regency and in 2019 increased to 72,165. The methods used in community service are blood pressure checks and hypertension education. The implementation procedure begins with registration, basic assessment, blood pressure checks, and hypertension education. The media used is a leaflet. The results of this activity obtained 15 participants with 33.3% having a history of hypertension and 46.6% when blood pressure checks showed hypertension results. Education is carried out by providing information on healthy lifestyle modifications and avoiding risk factors for hypertension. Uncontrolled hypertension can cause complications. This activity can be carried out continuously regarding education or counseling about hypertension